Penerapan dan Pengembangan Paragraf Bahasa Indonesia dalam Pendidikan Pembelajaran Mahasiswa - Edi Syahputra; Masita Hamidiyah; Nisa Fahria Nasution (Universitas Dehasen Bengkulu, 2022)
This journal discusses the Application and Development of paragraphs Indonesian Language in College Student Learning Education at the Faculty of Tarbiyah and Teacher Training. Evaluation is systematics that is carried out as a process to determine the value of a thing. Learning is a relatively permanent process of change in the curriculum as well as from the experience gained from training and practice that is strengthened. The lesson studied here is Indonesian language. Indonesian language is the language of unity that since the youth oath was pledged to become the national identity of the Indonesian nation. One of the materials studied is about paragraphs. A paragraph is a collection of several sentences related to each other and there is one main idea as a controller and an explanatory sentence as a support. This type of research is qualitative research and literature research (research library. As for the research instruments, they are observation and research as key instruments. The source of this research data is from the results of observations to the field, namely students and college students of the Faculty of Tarbiyah and Teacher Training of universities and literature reviews. As for the results of this study, there are only a few college students who answer with good grades. Meanwhile, the rest of us found strategies to avoid this.